Penric's fox : a fantasy novella in the world of the Five Gods - Bujold, Lois McMaster (Bujold, Lois McMaster. World of the five gods: Penric and Desdemona, 2018)
Some eight months after the events of Penric and the Shaman, Learned Penric, sorcerer and scholar, travels to Easthome, the capital of the Weald. There he again meets his friends Shaman Inglis and Locator Oswyl. When the body of a sorceress is found in the woods, Oswyl draws him into another investigation, and they must all work together to uncover a mystery mixing magic, murder, and the strange realities of Temple demons.